1964 - O Brasil Entre Ermas e Livros: Denial and Revisionism of the History - da Silva, Jose Alexandre; Colacios, Roger Domenech (Revista de Historia Social y de las Mentalidades, 2023)
This article aims to analyze the documentary “1964: o Brasil entre armas e livros” produced by the Brasil Paralelo company. This movie presents to the public a revisionistic proposal for the historic period of Brazilian Military Dictatorship, based on readings from the so-called extreme-right, centered on the figure of Olavo de Carvalho. The documentary is based on other interpretations of historical facts and counterfactual analyses, seeking to emphasize the supposed communist threat that haunted the national state throughout the 20th century until the present day. Those responsible for the documentary are not historians or specialists in any aspect of historical research, but they base their statements and arguments on testimonies and interviews with former guerrillas, right-wing intellectuals, and others. Using a traditional historical perspective, the documentary emphasizes superficial and problematic notions of history, with grotesque errors and more subtle ones. The analysis proposed here makes the discussion based on the relationship between history, historical revisionism, and denial, besides de analysis of the documentary format. As a result, the intention here is to highlight the ways in which historical revisionism and denial are being presented today by the extreme right in social media and using movies with easy access.
Keywords: History of Brazil; Revisionism; Brasil Paralelo; Military Dictatorship; Documentary